Central mucoepidermoid carcinoma of the mandible deriving from odontogenic cyst: A case report and review of the literature. Issue 8 (3rd August 2022) - Loreti, Andrea; Ornella, Abate; Arelli, Floriana; Spallone, Diana; Bruno, Edoardo; De Luca, Pietro; Costarelli, Leopoldo; Camaioni, Angelo
Abstract: Mucoepidermoid Carcinoma (MEC) it can origin from a mandibular odontogenic cyst. We report the case of a 63‐year‐old man with MEC of the right retromolar trigonum of the mandibula. We performed a wide mandibular excision and immediate reconstruction with a fibula bone free flap. Abstract : Treatment of mandibular mucoepidermoid carcinoma central type can be carried out safely and aesthetical valid through a wide segmental mandibular excision with an immediate reconstruction with fibula bone‐free flap and a postoperative RT.